Transnationalism and Conjugality: The Angola/Portugal Case - Grassi, Marzia (2016)
This chapter explores the main results of the research project “Places and Belongings: conjugality between Angola and Portugal”1 which in the context of contemporary studies on families and transnational lives, analyzes the emergence of new forms of conjugality in heterosexual couples who live “apart together” in and between Portugal and Angola. Based on empirical evidence substantiating a recent upturn in migration flows from Portugal to Angola—which is twice that going in the other direction—this project examines the belief that labor-driven migration is a phenomenon that runs from developing to developed countries.